Nano-fertilizers for Sustainable Agriculture - Abhigna, D.; Lakshman, K.; Prasad, P. N. Siva (Chronicle of Bioresource Management, 2023)
Today’s farming community across the world is facing a wide spectrum of challenges in crop production systems. The important ones are climate change, food and nutritional security, depletion of soil fertility, decline in response to applied fertilizers, decline in water table depth, increased disease and pest incidence in crops and socio-economic issues of the farmers. So, it would be difficult to produce enough food to feed the ever increasing population, which is expected to cross nine billion by 2050. Nanotechnology is having the huge potential to address these challenges with its applications in the field of agriculture. Traditional fertilizers are not only costly for the farmers, but also harmful to human beings and to the environment. This has led to the search for Environment friendly fertilizers, particularly those with high nutrient-use efficiency. The benefits of Nano-fertilizers or Nano-materials are unquestionably opening new approaches towards precision farming and sustainable agriculture.